The influence of roots on mycorrhizal fungi, saprotrophic microbes and carbon dynamics in a low‐phosphorus Eucalyptus forest under elevated CO2. (3rd June 2021) - Castañeda‐Gómez, Laura; Powell, Jeff R.; Ellsworth, David S.; Pendall, Elise; Carrillo, Yolima
Abstract: Elevated atmospheric carbon dioxide (eCO2 ) can impact soil organic matter (SOM) dynamics by changing the rates of carbon (C) losses and gains. In the rhizosphere, these changes are usually assumed to be the result of root‐mediated eCO2 impacts on saprotrophic microbes via altered below‐ground C allocation. This C allocation can also impact mycorrhizal fungi and their role in SOM dynamics. However, direct field quantifications of the influence of roots on both mycorrhizal fungi and saprotrophs together with SOM dynamics in forests exposed to eCO2 are rare. This is especially true in phosphorus (P)‐limited systems, even though ecosystem responses to eCO2 are known to depend on P availability. We assessed root mediation of eCO2 impacts on saprotrophs, mycorrhizal fungi, and C dynamics of root litter and mineral soil C (SOM‐C) in a mature, P‐limited Eucalyptus woodland exposed to eCO2 . We used a novel nested‐mesh‐bag method to manipulate roots access to the substrates in a 1‐year field incubation. We used an isotopic approach to trace C dynamics and performed a comprehensive microbial community analysis, along with nutrients and enzymatic activity measurements. Roots increased microbial biomass, fungal:bacterial ratio, plant‐derived C gains and substrate C losses while decreasing P availability and specific enzymatic activity. eCO2 increased bacterial relative abundance in root litter and protozoa in SOM‐C, but it did not enhance root impacts or mycorrhizal fungi biomass. Our combination of in‐situ approaches allowed us to demonstrate that while roots have multiple impacts on soil microbial communities and C dynamics, they are not the main drivers of responses to eCO2 in this P‐limited forest. Other factors beyond enhanced root‐derived below‐ground C inputs such as seasonality of nutrient and water availability, and shifts in plant communities may be more important in modulating eCO2 impacts on soil dynamics in P‐limited systems. ​ A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article. ​